2016
DOI: 10.1111/gwmr.12146
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Resistance Heating of Clay Layers in Water‐Saturated Sand

Abstract: Electrical resistance heating (ERH) experiments were performed in a two‐dimensional water‐saturated porous medium comprising an electrically conductive, low‐permeability clay lens embedded within a less electrically conductive, higher permeability silica sand. These were compared to experiments performed in homogeneous silica sand. All experiments were performed in the absence of a non‐aqueous phase liquid (NAPL) or dissolved volatile organic compound (VOC). Temperature monitoring showed preferential heating i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 17 publications
0
7
0
Order By: Relevance
“…The heat transfer effects of ERH technology on soils differs significantly, due to the fact that electrical conductivity of different soil types vary by 0-200 times. In general, clay has higher electrical conductivity than sand and heats up faster (Martin et al 2016). SEE technology is inappropriate for the treatment of low permeability media or heterogeneous sites since the soil permeability varies by 10 2 -10 4 times (Suthersan et al 2016).…”
Section: Mechanisms Of Heating Processmentioning
confidence: 99%
See 3 more Smart Citations
“…The heat transfer effects of ERH technology on soils differs significantly, due to the fact that electrical conductivity of different soil types vary by 0-200 times. In general, clay has higher electrical conductivity than sand and heats up faster (Martin et al 2016). SEE technology is inappropriate for the treatment of low permeability media or heterogeneous sites since the soil permeability varies by 10 2 -10 4 times (Suthersan et al 2016).…”
Section: Mechanisms Of Heating Processmentioning
confidence: 99%
“…on the surface of the soil particles, and the gas nucleates here first due to the geometry of the gas cavities, local wetting characteristics, capillary pressure and priority contact angles. Experimental results have shown that when the sites are heterogeneous, the generation of bubble begins with nucleation in the gas cavities on the surface of soil particles at the high-low permeability interface and then extends outward (Martin et al 2017, Martin et al 2016. Contaminants are preferentially removed in areas with high permeability, whereas the areas with low permeability may maintain high pollutant concentrations (Martin et al 2017, Kevin et al 2021.…”
Section: Gas Formationmentioning
confidence: 99%
See 2 more Smart Citations
“…A promising technique for clay geologies is electrical resistance heating (ERH) and related technologies such as ET-DSP TM . Laboratory experiments have demonstrated preferential heating in clay materials and preferential phase change at interfaces with soils with lower displacement pressures [1]. Other experiments have quantified gas production in the interior of clay lenses, which may exist as an unconnected phase within the low permeability clay [2].…”
Section: Extended Abstractmentioning
confidence: 99%